2013
DOI: 10.14309/00000434-201310001-00396
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-Induced Hepatitis B Reactivation

Abstract: Background. It has recently been reported that hepatitis B (HBV) reactivation often occurs after the use of rituximab and stem cell transplantation in patients with lymphoma who are hepatitis B surface antigen (HBsAg) negative. However, clinical data on HBV reactivation in multiple myeloma (MM) is limited to only a few reported cases. Bortezomib and lenalidomide have remarkable activity in MM with manageable toxicity profiles, but reactivation of viral infections may emerge as a problem. We present a case of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Bortezomib and thalidomide are used in treating MM. Several cases of hepatitis B infection associated with BOR have been reported . CPA, DXR, and melphalan (L‐PAM) are also used in the treatment of MM, and lenalidomide may be indicated for MM.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib and thalidomide are used in treating MM. Several cases of hepatitis B infection associated with BOR have been reported . CPA, DXR, and melphalan (L‐PAM) are also used in the treatment of MM, and lenalidomide may be indicated for MM.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with HBV infection who subsequently develop MM are at risk for reactivation following chemotherapy, particularly following immunosuppressive chemotherapy. Several recent studies found a significantly higher occurrence of HBV reactivation and/or hepatic damage after patients with HBV infection underwent chemotherapy, especially protocols containing high doses of glucocorticoids or proteasome inhibitor bortezomib, which are the commonly used agents in the treatment of MM. The mechanism of HBV reactivation in association with chemotherapy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HBV DNA contains a glucocorticoid‐responsive element that reportedly facilitates HBV replication . Bortezomib may alter the number and function of CD8 T cells and CD56 natural killer cells, and HBV reactivation may be attributable to the effect of bortezomib on cell‐mediated immunity . In addition, patients with concurrent MM and HBV infection reportedly experience more and earlier hepatic adverse events while undergoing chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bortezomib, mainly by inhibition of the NF‐κB pathway, may increase the risk of viral infections. Clinical data on HBV reactivation in patients receiving bortezomib in MM are limited to only a few reported cases . Li et al .…”
Section: Discussionmentioning
confidence: 99%